(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Novel Coronavirus, COVID-19 which was created in the city Wuhan of China has dramatically spread in many countries of the world. According to public health data compiled by Johns Hopkins University, as of August 14, 2020, just 5 months after the WHO (World Health Organization) declared the new coronavirus (Covid-19) pandemic, due to Covid-19 more than 21 million cases was Covid-19 and 761,000 deaths have been reported. This period disrupted the found Corana positive social and economic systems worldwide